Akkermansia muciniphila counteracts the deleterious effects of dietary emulsifiers on microbiota and host metabolism. Issue 5 (16th January 2023) - Daniel, Noëmie; Gewirtz, Andrew T; Chassaing, Benoit
Abstract : Background: Accumulating evidence indicates that some non-absorbed food additives, including emulsifiers carboxymethylcellulose (CMC) and polysorbate 80 (P80), can negatively impact intestinal microbiota, leading to microbiota encroachment, chronic low-grade intestinal inflammation and, subsequently, promotion of metabolic dysregulations. Detrimental impacts of emulsifier consumption on gut microbiota include depletion of the health-associated mucus-fortifying bacteria, Akkermansia muciniphila . Objective: Investigate, in mice, the potential of administration of exogenous A. muciniphila as a means to protect against detrimental impacts of emulsifiers. Results: Daily oral administration of A. muciniphila prevented phenotypic consequences of consumption of both CMC and P80, including hyperphagia, weight gain and dysglycaemia. A. muciniphila administration also counteracted the low-grade intestinal inflammation-induced CMC and P80. Furthermore, A. muciniphila supplementation prevented the proximal impacts of CMC and P80 on gut microbiota that are thought to drive low-grade chronic inflammation and metabolic dysregulations. Specifically, A. muciniphila prevented alterations in species composition and encroachment of gut microbiota that were otherwise induced by CMC and P80. Remarkably, we finally report that CMC and P80 altered the colonic transcriptome, while A. muciniphila largely protected against these alterations. Conclusion: Daily administration of A. muciniphila protects against the detrimental impact of emulsifiers on both the microbiota and host. These results support the notion that use of A. muciniphila as a probiotic can help maintain intestinal and metabolic health amidst the broad array of modern stresses that can promote chronic inflammatory diseases.